2017
DOI: 10.5194/acp-17-14695-2017
|View full text |Cite
|
Sign up to set email alerts
|

Estimating uncertainties in the SBUV Version 8.6 merged profile ozone data set

Abstract: Abstract. The combined record of total and profile ozone measurements from the solar backscatter ultraviolet (SBUV) and SBUV/2 series of instruments, known as the SBUV Merged Ozone Data (MOD) product, constitutes the longest satellite-based ozone time series from a single instrument type and as such plays a key role in ozone trend analyses.Following the approach documented in to analyze the merging uncertainties in the MOD total ozone record, we use Monte Carlo simulations to estimate the potential for uncert… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 27 publications
6
34
0
Order By: Relevance
“…The Merged-SWOOSH/GOZCARDS and Merged-SBUV results presented here combine these two pairs of composites , which show slightly different spatial variability (see Fig. S1) Harris et al, 2015;Steinbrecht et al, 2017;Frith et al, 2017). Part of the reason is related to offsets and drifts in the data that continue to be one of the largest remaining sources of uncertainty within, and between, ozone composites Ball et al, 2017;Frith et al, 2017).…”
Section: Merged-swoosh/gozcards Andmentioning
confidence: 99%
See 2 more Smart Citations
“…The Merged-SWOOSH/GOZCARDS and Merged-SBUV results presented here combine these two pairs of composites , which show slightly different spatial variability (see Fig. S1) Harris et al, 2015;Steinbrecht et al, 2017;Frith et al, 2017). Part of the reason is related to offsets and drifts in the data that continue to be one of the largest remaining sources of uncertainty within, and between, ozone composites Ball et al, 2017;Frith et al, 2017).…”
Section: Merged-swoosh/gozcards Andmentioning
confidence: 99%
“…S1) Harris et al, 2015;Steinbrecht et al, 2017;Frith et al, 2017). Part of the reason is related to offsets and drifts in the data that continue to be one of the largest remaining sources of uncertainty within, and between, ozone composites Ball et al, 2017;Frith et al, 2017). These artefacts can be largely accounted for using the Bayesian integrated and consolidated (BASIC) methodology developed by Ball et al (2017), which we apply to both pairs of data separately; examples of corrected time series in the lower stratosphere are given in Fig.…”
Section: Merged-swoosh/gozcards Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we have analysed Solar Backscatter Ultraviolet Radiometer (SBUV; McPeters et al, 2013;Frith et al, 2017) and lidar ozone profile data from the Network for the Detection of Atmospheric Composition Change (NDACC) as part of the Long-term Ozone Trends and Uncertainties in the Stratosphere (LOTUS) project (http://igaco-o3.fmi.fi/ LOTUS/index.html, last access: 2 May 2018). The project aims at providing support and input to the WMO/UNEP 2018 Ozone Assessment for a better understanding of ozone trends and their significance as a function of altitude and latitude, nearly 20 years after the peak of ozone depleting substances in the stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Phys. Discuss., https://doi.org /10.5194/acp-2018- (Frith et al, 2017 shown are estimates of the partial column from the Bodeker Scientific Vertical Ozone (BSVertOzone) database, which is based on a compilation of satellite, balloon and ground-based measurements (Bodeker et al, 2013). …”
Section: ) Summary and Conclusionmentioning
confidence: 99%